The use of indicators in the pre-analytical phase as a laboratory management tool - Fabio Triachini Codagnone; Sibelle Mattos Flores Alencar; Wilson Shcolnik; Sergio Roberto da Silva Chaves; Luciano Andrade Silva; Victor Hugo Oliveira Henriques; Luana Carrilho Spitz (Jornal Brasileiro de Patologia e Medicina Laboratorial, 2014)
Introduction:Efficient laboratory services are the basis of modern health systems. Scientific innovations have contributed to substantial improvements in the laboratory environment, but errors still persist. These errors are classified as pre-analytical, analytical and post-analytical, according to the time of occurrence.Objective:To evaluate the frequency of pre-analytical errors in the clinical laboratory service of a military hospital.Methods:A total of 329,582 tests were performed in the clinical laboratory of Hospital Naval Marcílio Dias (HNMD) from August to October 2012, and pre-analytical errors were documented.Results:The most frequent cause of the observed pre-analytical errors was hemolysis (27.54%), followed by samples not received (25.43%) and insufficient sample volume (18.49%). The samples from the Integrated Home Care Service (SIAD) showed the highest frequency of errors (3.38%), followed by those from the inpatient (0.76%) and the outpatient departments (0.21%).Conclusion:Our study demonstrates the importance of managing laboratory pre-analytical quality in order to ensure service excellence.